Efficacy of Alteplase in a Mouse Model of Acute Ischemic Stroke: A Retrospective Pooled Analysis. Issue 5 (May 2016) - Orset, Cyrille; Haelewyn, Benoit; Allan, Stuart M.; Ansar, Saema; Campos, Francesco; Cho, Tae Hee; Durand, Anne; El Amki, Mohamad; Fatar, Marc; Garcia-Yébenes, Isaac; Gauberti, Maxime; Grudzenski, Saskia; et al.
Abstract : Background and Purpose—: The debate over the fact that experimental drugs proposed for the treatment of stroke fail in the translation to the clinical situation has attracted considerable attention in the literature. In this context, we present a retrospective pooled analysis of a large data set from preclinical studies, to examine the effects of early versus late administration of intravenous recombinant tissue-type plasminogen activator. Methods—: We collected data from 26 individual studies from 9 international centers (13 researchers; 716 animals) that compared recombinant tissue-type plasminogen activator with controls, in a unique mouse model of thromboembolic stroke induced by an in situ injection of thrombin into the middle cerebral artery. Studies were classified into early (<3 hours) versus late (≥3 hours) drug administration. Final infarct volumes, assessed by histology or magnetic resonance imaging, were compared in each study, and the absolute differences were pooled in a random-effect meta-analysis. The influence of time of administration was tested. Results—: When compared with saline controls, early recombinant tissue-type plasminogen activator administration was associated with a significant benefit (absolute difference, −6.63 mm 3 ; 95% confidence interval, −9.08 to −4.17; I 2 =76%), whereas late recombinant tissue-type plasminogen activator treatment showed a deleterious effect (+5.06 mm 3 ; 95% confidence interval, +2.78 to +7.34; I 2 =42%; P int <0.00001). Results remained unchanged after subgroup analyses. Conclusions—: Our results provide the basis needed for the design of future preclinical studies on recanalization therapies using this model of thromboembolic stroke in mice. The power analysis reveals that a multicenter trial would require 123 animals per group instead of 40 for a single-center trial. Abstract : Supplemental Digital Content is available in the text.